2006
DOI: 10.1002/jbm.b.30599
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of alumina‐ and zirconia ceramics used for crown and bridge restorations

Abstract: The lifetime of a ceramic is dependent on the presence of incidental cracks and their gradual propagation under the conditions of the oral cavity. The objective of this study was to examine the long-term strength of glass-infiltrated alumina- and various zirconia ceramics currently used in CAD/CAM systems to manufacture crown and bridge frameworks. Fracture mechanics were applied to determine characteristic strength (sigma(omicron)), Weibull modulus (m), fracture toughness (K(Ic)), and the subcritical crack gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 22 publications
1
65
0
13
Order By: Relevance
“…23 Tinschert compared lifetime of different metal-free core for FPD and reported that zirconia-ceramic with alumina oxide had the highest initial and most favorable long-term strength. 24 fundamental to obtain zirconia (ZrO 2 ) frameworks with correct shape and dimension in order to ensure mechanical resistance of restoration. This aspect must be carefully considered when realizing a metal-free FPD.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…23 Tinschert compared lifetime of different metal-free core for FPD and reported that zirconia-ceramic with alumina oxide had the highest initial and most favorable long-term strength. 24 fundamental to obtain zirconia (ZrO 2 ) frameworks with correct shape and dimension in order to ensure mechanical resistance of restoration. This aspect must be carefully considered when realizing a metal-free FPD.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Esse sistema cerâmico apresenta valores médios de resistência à flexão variando entre 700 e 1500 MPa e tenacidade à fratura entre 4,4 e 9,4 MPa.m 1/2 (Liu;Chen, 1991;Kosmac et al, 1999;Tinschert et al, 2000;Luthardt et al, 2002;Guazzato et al, 2004a;Tinschert et al, 2007;Yilmaz et al, 2007;Oilo et al, 2008;Taskonak et al, 2008a). Foram reportados, para a YZ, valores de dureza ao redor de 12 GPa e módulo de elasticidade entre 220 e 240…”
Section: Zircônia Tetragonal Parcialmente Estabilizada Com óXido De íunclassified
“…Além disso, tensões residuais de compressão, que irão melhorar a resistência, também são introduzidas devido às diferenças no coeficiente de expansão térmica da alumina e do vidro (Giordano et al, 1995). O ICA apresenta uma resistência à flexão entre 300-600 MPa (Zeng et al, 1996;Tinschert et al, 2000;Chong et al, 2002; (Guazzato et al, 2002;Rizkalla;Jones, 2004;Guazzato et al, 2004b;Tinschert et al, 2007). Esse sistema é indicado como infra-estrutura em restaurações unitárias anteriores e posteriores e PPFs em dentes anteriores (Probster, 1996).…”
Section: In-ceram Zircônia -Izunclassified
See 2 more Smart Citations